A MassTag PCR Assay for the Syndromic Detection of Pathogens that can cause Neurological Disease - Williams, David; Menegola, David; Moody, K.; Yang, L.; Levy, A.; Briese, T.; Tokarz, R.; Harnett, G.; MacKenzie, John; Smith, D.; Lipkin, W. (Australian Society for Microbiology, 2011)
MassTag PCR is a novel technology for the rapid, sensitive and simultaneous detection of multiple gene sequences. This technique utilises a library of molecular tags, each unique in its molecular weight. MassTags are conjugated to oligonucleotide primers using a UV-cleavable linker that enables separation of primer and tag. Different primers are labelled each with a different molecular weight tag and are used to amplify target nucleic acids in a multiplex RT-PCR. After removing unincorporated primers, tags are released by UV irradiation and analysed using a single quadrupole liquid chromatography mass spectrometer (LC/MS). Thus, amplification of the gene target produces a unique dual signal in LC/MS analysis that allows its identification. Neurological disease represents a diagnostic challenge, with over 100 microbial agents associated with infection of the central nervous system (CNS). We have developed a panel of multiplex MassTag PCR assays to specifically detect >30 microbial agents that cause CNS infections, relevant to an Australasian diagnostic setting. Three assays were developed using optimised PCR chemistry and thermocycling conditions to detect: (i) common microbial causes of disease (11-plex); (ii) arthropod-borne and zoonotic infections (14-plex); and (iii) rare or uncommon causes (11-plex). The performance of these assays was evaluated in a clinical diagnostic laboratory using CSF specimens and sensitivity estimates for each target were established using synthetic nucleic acids. Our findings indicate that MassTag PCR offers an inexpensive and sensitive diagnostic platform suitable for high-throughput testing.